Learned Immunosuppressive Placebo Response Attenuates Disease Progression in a Rodent Model of Rheumatoid Arthritis. Issue 4 (30th March 2020) - Lückemann, Laura; Stangl, Hubert; Straub, Rainer H.; Schedlowski, Manfred; Hadamitzky, Martin
Abstract : Objective: Patients with chronic inflammatory autoimmune diseases benefit from a broad spectrum of immunosuppressive and antiproliferative medication available today. However, nearly all of these therapeutic compounds have unwanted toxic side effects. Recent knowledge about the neurobiology of placebo responses indicates that associative learning procedures can be utilized for dose reduction in immunopharmacotherapy while simultaneously maintaining treatment efficacy. This study was undertaken to examine whether and to what extent a 75% reduction of pharmacologic medication in combination with learned immunosuppression affects the clinical outcome in a rodent model of type II collagen–induced arthritis. Methods: An established protocol of taste‐immune conditioning was applied in a disease model of chronic inflammatory autoimmune disease (type II collagen–induced arthritis) in rats, where a novel taste (saccharin; conditioned stimulus [CS]) was paired with an injection of the immunosuppressive drug cyclosporin A (CSA) (unconditioned stimulus [US]). Following conditioning with 3 CS/US pairings (acquisition), the animals were immunized with type II collagen and Freund's incomplete adjuvant. Fourteen days later, at the first occurrence of clinical symptoms, retrieval was started by presenting the CS together with low‐dose CSA as reminder cues to prevent the conditioned response from being extinguished. Results: This "memory‐updating" procedure stabilized the learned immune response and significantly suppressed disease progression in immunized rats. Clinical arthritis score and histologic inflammatory symptoms (both P < 0.05) were significantly diminished by learned immunosuppression in combination with low‐dose CSA (25% of the full therapeutic dose) via β‐adrenoceptor–dependent mechanisms, to the same extent as with full‐dose (100%) pharmacologic treatment. Conclusion: These results indicate that learned immunosuppression appears to be mediated via β‐adrenoceptors and might be beneficial as a supportive regimen in the treatment of chronic inflammatory autoimmune diseases by diminishing disease exacerbation.